Mekanisme Pembiayaan Syariah pada Baitul Māl wat Tamwīl (BMT) Amanah Kota Buton Tengah dalam Tinjauan Fikih Muamalah - Saadal Jannah; Sri Ujiana Putri; Asma Asma (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, Indonesia, 2023)
This study aims to find out and understand the mechanism of sharia financing at the Baitul Māl wat Tamwīl (BMT) Amanah, Central Buton City in a review of muamalah fiqh. This research uses descriptive qualitative field research, using normative and sociological approaches. The research results found as follows; first, the sharia financing mechanism for BMT Amanah, namely; members must follow established procedures, such as; (1). The customer comes directly to the BMT office to submit a financing application, (2). The customer must include requirements such as a photocopy of husband and wife's KTP, family card, marriage certificate, and guarantee letter, (3). Files go to BMT, (4). Conducted surveys. Then the BMT conducts a survey analysis meeting, conducts contracts, disburses funds, conducts coaching (if deemed necessary by the customer) and confiscation of collateral if the customer is unable to pay his installment obligations and is in disagreement with the agreement of both parties. Second, the financing mechanism at BMT Amanah, when viewed from the fiqh muamalah, most of the mechanisms are appropriate because the pillars and conditions for the validity of the contract have been fulfilled. With an agreement between BMT Amanah and the customer and witnessed by witnesses from BMT and each party to carry out obligations according to the agreement. But the principle in the practice of bai' biṡaman ājil is that there are things that are not fully in accordance with the fiqh principles of muamalah, namely in the first model, the goods are not handed over to the BMT, but the goods are taken directly by the customer without first being handed over to the BMT. The implication of this research is that BMT Amanah should be more active in disseminating its products to the public, so that people are more familiar with BMT Amanah and are then interested in becoming its members.